Perbandingan Nyeri Pemasangan Infus Menggunakan Tehnik Distraksi Visual Kartu - Jupri Kartono; Fiki Nurfitri (Jurnal Kesehatan Panca Bhakti Lampung (JKPBL), 2022)
Children who are hospitalized will receive measures and treatments according to their basic needs and illness. One of the routine actions is the installation of infusion that causes pain. The aim of this study was to determine the level of pain infusion in preschool children performed and not done by visual distraction card techniques. This research method uses a quantitative method with a case control design approach where pain response measurements are carried out on 30 respondents who are divided into two groups, those are the group treated with the card visual distraction technique and the group not treated with the card visual distraction technique. Researchers used the Wong Baker Pain Rating Scale to measure respondents' pain levels. Data analysis uses the Mann Withney statistical test. The results obtained after the card visual distraction technique was given to 15 respondents in the intervention group experienced moderate and mild pain levels while in 15 respondents the control group was not given intervention the level of pain was moderate and severe categories, further analysis using statistical tests obtained p value 0,000 which means there Significant influence between the level of pain infusion installation and card visual distraction techniques. The conclusion was that the card visual distraction technique was able to reduce the level of pain of preschool children when infusion was not performed.